2016
DOI: 10.4049/jimmunol.1500351
|View full text |Cite
|
Sign up to set email alerts
|

α-NAC–Specific Autoreactive CD8+ T Cells in Atopic Dermatitis Are of an Effector Memory Type and Secrete IL-4 and IFN-γ

Abstract: Autoreactivity may play a critical role in the chronification of atopic dermatitis (AD). Several studies showed that AD patients produce IgE Abs specific for autoantigens, and we described Th as well as CD8+ T cells specific for the autoallergen Hom s 2, the α-chain of the nascent polypeptide-associated complex (α-NAC). This study aimed to investigate the frequency and inflammatory phenotype of autoallergen-specific CD8+ T cells. CD8+ T cell immunodominant epitopes of α-NAC were mapped by applying prediction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 77 publications
(81 reference statements)
0
42
0
1
Order By: Relevance
“…Importantly, the development of IgE antibodies to a wide range of exogenous and endogenous agents requires antigen specific T cells for inducing IgE class switching, cells that might be present at lower frequencies in AD skin, both in lesional and in nonlesional skin. On a cellular level, T‐cell autoreactivity to Hom s2 (alpha‐chain of the nascent polypeptide‐associated complex (α‐NAC)) has been demonstrated . T cells activated by Hom s2 in atopic individuals are memory cells that produce IL‐4 (Th2/Tc2 T cells).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the development of IgE antibodies to a wide range of exogenous and endogenous agents requires antigen specific T cells for inducing IgE class switching, cells that might be present at lower frequencies in AD skin, both in lesional and in nonlesional skin. On a cellular level, T‐cell autoreactivity to Hom s2 (alpha‐chain of the nascent polypeptide‐associated complex (α‐NAC)) has been demonstrated . T cells activated by Hom s2 in atopic individuals are memory cells that produce IL‐4 (Th2/Tc2 T cells).…”
Section: Discussionmentioning
confidence: 99%
“…T cells activated by Hom s2 in atopic individuals are memory cells that produce IL‐4 (Th2/Tc2 T cells). Hom s2‐reactive T cells have been detected by HLA‐A*02 tetramers at higher frequency in AD patients vs controls, both in central memory and effector memory subsets, and might therefore constitute a possible disease elicitor.…”
Section: Discussionmentioning
confidence: 99%
“…It is also observed that adult AD has increased frequencies of IL-22-producing CD4 and CD8 T cells within the skin-homing population [4] and that significantly elevated autoreactive CD8 + T cells in AD are effector memory type cells [5]. IL-13 is a key Th2 cytokine involved in atopic disease, while IFN-γ and IL-22 play pivotal roles in host defence against microbes and in the development of chronic inflammatory diseases [6].…”
Section: Introductionmentioning
confidence: 99%
“…While past work has suggested that HDM is a trigger of AD, the HDM APT skin phenotype does not fully reproduce AD at the molecular level, even in the background of nonlesional AD skin. Other work has identified autoantigens that drive T cell activation in this disease …”
Section: Discussionmentioning
confidence: 98%